P11.13 Radiotherapy combined with a multimodal imaging approach in a glioblastoma preclinical model. (6th September 2019) - Salvatore, D; Shaw, G; Wright, J; Teh, I; Koch-Paszkowski, J; Murray, L; Scarsbrook, A; Schneider, J; Ottobrini, L; Short, S
Abstract: BACKGROUND: Glioblastoma multiforme (GBM) carries a poor prognosis, partly due to biological and anatomical heterogeneity. Although radiotherapy (RT) is effective, high doses damage surrounding healthy tissues. Multimodal imaging with Magnetic Resonance (MRI) and Positron Emission Tomography (PET) may represent a useful approach for identifying GBM heterogeneity and visualising metabolic tumour properties. PET radiotracer [18F]-fluciclovine is preferentially accumulated in gliomas compared to healthy brain tissue via the cellular transport systems, LAT1 and ASCT2. In this study the effect of fractionated RT using multimodal imaging including [18F]-fluciclovine uptake and immunohistochemistry (IHC) in a GBM preclinical model will be validated. MATERIAL AND METHODS: Two C57BL/6J mice cohorts were injected intracranially (i.c.) with murine CT2A-luc cells and subsequently submitted to multiparametric MRI and [18F]-fluciclovine PET imaging during hemi-brain RT (3Gy on 2 days/each week) for maximum 25 days after i.c. injection. Brains were collected for IHC characterization including LAT1 and ASCT2 staining. RESULTS: Preliminary data showed that both MRI and PET were effective modalities to track tumour growth in this model. PET data revealed up to greater than 3-fold increase in SUVmax from regions of interest around the tumour site compared to healthy brain tissue. Time activity curves showed a steady increase in tumour uptake over 90 minutes. MRI showed a 25% increase in T2 values in tumours relative to unaffected contralateral regions. Confirmation of treatment response through matched imaging and IHC are ongoing, from which changes in glioma cell biology as well as amino acid transporter protein levels will be analysed. CONCLUSION: These preliminary results show that multimodal imaging presents novel data in the assessment of treatment response in this model and will permit parallel IHC analyses to better define GBM tumour heterogeneity aligned with imaging changes. These data will also inform an on-going clinical study using the same imaging modalities. Work at authors' labs are supported by an Investigator initiated project from Blue Earth Diagnostics (AS, SCS) and a University of Leeds Biswas studentship (SCS, DS). Daniela Salvatore is also supported by a Scholarship provided by Molecular and Translational Medicine Doctorate School of University of Milan (Italy).